Materials for Buildings and Structures 2000
DOI: 10.1002/3527606211.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect in Compression of High Strength Fibre Reinforced Concrete Cylinders Subjected to Concentric and Eccentric Loads

Abstract: Tests results obtained as a part of a study of size-effects on the compressive behavior of axially and eccentrically loaded plain and fibre reinforced concrete members are presented. The specimens were geometrically similar, having circular cross-sections with diameters of 60 and 100 mm, and varying in length from 120 to 400 mm. Several types of fibres (steel and synthetic) were added to the high strength matrices at a constant volume percentage of 2 % to evaluate their influence on the behavior of the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…In this section, a comparison is presented between the experimental results carried out by Campione and Mindless 28,29 and the theoretical predictions for the size effects on the dissipated energy density and on the compressive strength obtained respectively from the fractal laws of equations (7) and (8). The comparison regards geometrically similar cylindrical specimens with base diameters of 60, 100 and 150 mm and with fixed slenderness (height over diameter) equal to 2.…”
Section: Comparison Between Theoretical and Experimental Resultsmentioning
confidence: 96%
“…In this section, a comparison is presented between the experimental results carried out by Campione and Mindless 28,29 and the theoretical predictions for the size effects on the dissipated energy density and on the compressive strength obtained respectively from the fractal laws of equations (7) and (8). The comparison regards geometrically similar cylindrical specimens with base diameters of 60, 100 and 150 mm and with fixed slenderness (height over diameter) equal to 2.…”
Section: Comparison Between Theoretical and Experimental Resultsmentioning
confidence: 96%
“…The effect of steel fiber on the compressive strength of concrete has been discussed in many studies, and resulted that, the presence of the SF has slightly affect the compressive strength of concrete, but overall effect is negligible in many cases. Many researchers [10,11] have observed increases in the compressive strength of concrete ranging from (0 -15%) for up to 1.5 percent by volume of fibers. while other researchers observed that, the increase in the compressive strength range from negligible in most cases to 23 % for SFRC for up to 2.0 percent by volume of fiber [12].…”
Section: Compressive Strength Of Sfrcmentioning
confidence: 99%